Proses dan Iklim Komunikasi Antarbudaya - Efrita, Neni (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Communication is a process (that is one of the characteristics of the communication), because the communication is dynamic, always in progress and change often. A process consists of several sequences that can be distinguished but not separated. Intercultural communication is as same as other communication process that is a process that is dynamic and interactive and transactional. Interactive intercultural communication is communication made by participants in the two-way communication / reciprocity (two way communication) but was still at a low stage. Communication climate is constructed as a situation, atmosphere conditions involving the mind or spiritual situation or participants’ communication feeling. Several key communication climates can be shown by the characteristic where there is no more pressure on the power of communication participants, the principles of openness to all; the atmosphere is capable of providing communication participants to be able to differentiate between personal interests and the interests of the group.